Analysis of Language Style in Utsman bin Affan's First Sermon Post Heartball: Taḥlīl Uslūb al-Lughah fī Khuṭbah ‘Uthmān ibn ‘Affān al-Ūlā ba‘da al-Ighmā’ - Raudhatul Jannah; Kurnia, Ulfa; Perdana, Dyah Adila (An-Nahdah Al-'Arabiyah, 2026)
This study examines the stylistic beauty of Uthman ibn Affan's first sermon after his appointment as the third caliph by highlighting five main aspects, namely phonology, morphology, syntax, semantics, and imagery. This study uses a qualitative approach with a stylistic analysis method on the Arabic sermon text which is studied descriptively-analytical. The results show that the dominance of nasal and vibrating consonants forms a distinctive phonological rhythm that strengthens the persuasive power of the sermon, while syntactic variations through al-taqdīm wa al-ta'khīr and the repetition of the lafaz al-ghurūr emphasize the rhetorical power and emphasis of meaning. Semantic analysis reveals the use of denotative and connotative meanings as well as the use of al-ṭibāq (antonymy) techniques that enrich the expression of meaning. From a morphological perspective, the use of terms such as abnā' al-dunyā reflects the depth of contextual messages that are moral and spiritual. The element of imagery, particularly jinās, not only enhances the sound of language but also emphasizes the relationship of meaning within the discourse of sermons. The novelty of this research lies in the application of a comprehensive stylistic analysis to the sermons of the early Islamic caliphs, which have so far been studied primarily historically and thematically. This finding confirms that the linguistic beauty of Uthman ibn Affan's sermons is not merely rhetorical ornamentation, but rather an effective medium for conveying moral and spiritual messages persuasively   تتناول هذه الدراسة جمال الأسلوب في خطبة عثمان بن عفان الأولى بعد توليه الخلافة الثالثة، مُسلطةً الضوء على خمسة جوانب رئيسية، هي: علم الأصوات، وعلم الصرف، وعلم النحو، وعلم الدلالة، والتصوير. وتعتمد الدراسة منهجًا نوعيًا مع تحليل أسلوبي لنص الخطبة العربية، الذي دُرِسَ وصفيًا تحليليًا. تُظهر النتائج أن غلبة الحروف الأنفية والساكنة المهتزة تُشكل إيقاعًا صوتيًا مميزًا يُعزز قوة الخطبة الإقناعية، بينما تُؤكد التنويعات النحوية من خلال "التقديم والإخراج" وتكرار "لفظ الغرور" على قوة البلاغة وتأكيد المعنى. ويكشف التحليل الدلالي عن استخدام المعاني الدلالية والإيحائية، فضلًا عن استخدام تقنيات "الطَباق" (التضاد) التي تُثري التعبير عن المعنى. من منظور صرفي، يعكس استخدام مصطلحات مثل "أبناء الدنيا" عمق الرسائل السياقية ذات الطابع الأخلاقي والروحي. ولا يقتصر دور الصور البلاغية، ولا سيما "الجنس"، على إثراء رنين اللغة فحسب، بل يؤكد أيضًا على ترابط المعاني في خطاب الخطب. وتكمن جدة هذا البحث في تطبيق تحليل أسلوبي شامل على خطب الخلفاء الراشدين، التي دُرست حتى الآن بشكل أساسي من منظور تاريخي وموضوعي. وتؤكد هذه النتيجة أن جمال خطب عثمان بن عفان اللغوي ليس مجرد زخرفة بلاغية، بل هو وسيلة فعالة لنقل الرسائل الأخلاقية والروحية بأسلوب مقنع.   Penelitian ini menelaah keindahan stilistika dalam khutbah pertama Utsman bin Affan setelah pengangkatannya sebagai khalifah ketiga dengan menyoroti lima aspek utama, yaitu fonologi, morfologi, sintaksis, semantik, dan imagery. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis stilistika terhadap teks khutbah berbahasa Arab yang dikaji secara deskriptif-analitis. Hasil penelitian menunjukkan bahwa dominasi konsonan nasal dan getar membentuk ritme fonologis khas yang memperkuat daya persuasif khutbah, sementara variasi sintaksis melalui al-taqdīm wa al-ta’khīr serta repetisi lafaz al-ghurūr menegaskan kekuatan retorika dan penekanan makna. Analisis semantik mengungkap pemanfaatan makna denotatif dan konotatif serta penggunaan teknik al-ṭibāq (antonimi) yang memperkaya ekspresi makna. Dari sisi morfologi, penggunaan istilah seperti abnā’ al-dunyā mencerminkan kedalaman pesan kontekstual yang bersifat moral dan spiritual. Unsur imagery, khususnya jinās, tidak hanya memperindah bunyi bahasa, tetapi juga mempertegas relasi makna dalam wacana khutbah. Kebaruan penelitian ini terletak pada penerapan analisis stilistika komprehensif terhadap khutbah khalifah awal Islam, yang selama ini lebih banyak dikaji secara historis dan tematik. Temuan ini menegaskan bahwa keindahan bahasa khutbah Utsman bin Affan bukan sekadar ornamen retoris, melainkan medium efektif dalam menyampaikan pesan moral dan spiritual secara persuasif.